Komunikasi Visual Dan Inovasi Fotocall Studio Melalui Akun Instagram @Fotocall.Studio - Putra, Arief Tri Hardiyanto (Jurusan Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jenderal Soedirman, 2025)
Visual communication and innovation have become important factors in the success of photography businesses in the digital era, especially through Instagram. This study aims to (1.) Identify the visual communication of the Fotocall Studio team in attracting audience attention through the Instagram account @Fotocall.Studio, (2.) Identify the innovations carried out by the Fotocall Studio team in attracting public attention through the Instagram account @Fotocall.Studio. The method used is descriptive qualitative with the Diffusion of Innovations theory, supported by method visual content analysis and service innovation. The results show that Fotocall Studio’s visual communication is realized through simple and easy-to-read typography, high-quality photography with a natural atmosphere, the use of dominant colors such as white, black, and pastel, layouts with clear information hierarchy, as well as consistent logo usage. The main innovation in the form of a self-photo photobooth service can be understood through Rogers’ five stages: knowledge, persuasion, decision, implementation, and confirmation, which have been proven to increase audience engagement, the number of bookings, and client satisfaction.